Sir Arthur Hesilrige and the development of civil war in England - Costa, DR (1988)
The thesis provides a detailed account of Hesilrige's involvement in the local politics of Leicestershire, tactical struggles at Westminster and the conflicts between Parliament's generals. In the process it casts light on the nature of the politics of the 1630s and early 1640s and indicates the reasons for Hesilrige's successes and failures in later years. It demonstrates the convergence of national and local grievances in government during the 1630s and suggests that central pressure on local government had similar effects elsewhere. It argues that the combined force of these grievances together with opposition to Laudian aggression produced a strong reaction which in Leicestershire led to Hesilrige's election to the parliaments of 1640. It traces the steps by which the opposition leaders were forced, in the absence of a settlement, to adopt increasingly confrontational tactics during 1641, and the part played by Hesilrige in this process. The drift to war in 1642 was accelerated by the struggle for control of the Leicestershire militia which brought together national and local conflicts. Hesilrige became an enthusiastic soldier and leading partisan of Sir William Waller's political army in the competition between military lobbies which intensified political divisions and bitterness at Westminster during 1643 and 1644. At the same time he remained interested in securing influence and power in his county and became involved in fresh conflicts there during 1644. Political battles at Westminster, the rivalry of the generals, and struggles in Leicestershire came to a head in late 1644 and early 1645 and propelled Hesilrige into a position of leadership amongst his allies in the Commons and of dominance in his own county. The question raised by his immersion in short-term tactical struggles during the early 1640s was whether he could make constructive use of power.